Surgical outcomes of inverted Papilloma: a retrospective review of endoscopic and external approaches - Abdullah, Baharudin; Abdullah, Kahairi; Ahmed Khan, Shamim; Hamzah, Mohamad (The Internet Scientific Publications, 2007)
Introduction: Inverted Papilloma is a benign sinonasal tumour which generates considerable interest because they can recur and undergo malignant transformation. Methodology : We performed a retrospective analysis of patients treated at Universiti Sains Malaysia Hospital to determine the surgical outcome of the external and endoscopic approaches. Ten patients with inverted papilloma who underwent the external and the endoscopic treatment between July 1999 and May 2005 were analysed. Results : The study group consisted of 8 male and 2 female patients with mean age of 48 years. The external approach was done in 7 cases whereby an endoscopic technique was done in 3 cases. The follow up period ranged from 3 to 50 months (mean, 20 months). Recurrence rate was 28 % for external approach and none for endoscopic approach. Conclusions : Endoscopic approach has a good surgical outcome in inverted papilloma but case selection plays an important role. Endoscopic technique has the advantage of less postoperative morbidity and also gives an advantage for second surgery by the external approach should a recurrence occur.